What can a text? Desire of writing against end of alterity (Simbiótica. Revista Eletrônica, 2022)
Reduction of writing is one of the most important phenomena of our time. It is directly linked to the most diverse impositions coming from digital devices, that force a hypertrophy of response and reaction, while decreasing size and potency of texts. This impoverishes the scene of writing: it spreads everywhere, so, it is no longer located anywhere. Precisely for this reason, the body that writes and the landscape of this body are lost, also the experiencing of alterity and unfamiliar. Writing as an exercise of attention to language (in literature, in the epistle) that still maintains the possibility of building a place of democratic relationships and ways, since emptying language is, in itself, fertilizing violence.Keywors: Scene of writing; Language; Absence; Alterity.